Koszty uruchomienia produkcji nowych wyrobów w przedsiębiorstwie przemysłu maszynowego - Brzeziński, Alfons (Wydział Prawa i Administracji UAM, 1966)
The 5-year plan for the years 1966—70 poses to the machine industry very serious production tasks with respect to the volume of production as well as to the aspect of quality. The improvement in the. quality and standard of produced commodities becomes thus one of the fundamental tasks in the process of technical development. In the light of said tasks, a greater role than was the case hitherto, will play the costs of starting up production of new goods, which constitute the most important part of overall costs involved with introduction of new technique in the machine industry. The present situation with regard to registration and analysis of costs in the drive of technical development should be regarded as unsatisfactory. The present terminology needs some precision. There are no stable and uniform criteria of classifying various types of works to the costs of new production, what in turn makes practilcally impossible to regard the statistical data compiled in different reports as a proper measure-rod in the endeavours of technical development. That measure- -rod can neither be assumed by the amount of money drawn for this purpose from the special Fund for Technological and Economical Progress. The problem of costs in starting up production of new machines should be approached from the ,point of view of two of their financial sources: the turnover means or the Fund for Technological and Economical Progress. The analysis of existing regulations shows some inconsistencies in regard to the scope of works financed from the above mentioned two sources. The importance of assessing proper costs in getting started new production reflects itself mainly in two aspects: in the planning of development of technical progress and in the assessment of economic efficiency in undertakings of technical progress. The improvement in the economic account of costs is thus strictly related to the optimalization of economic decisions. There exists a great chance of remedying the situation in that field of activities of enterprises — by introducing electronic computes for data processing.